Respuesta :
[tex]m = \frac{2 - 4}{ - 2 + 6} \\ \frac{ - 2}{4} = \frac{ - 1}{2} \\ y - 2 = \frac{ - 1}{2} (x + 2) \\ y - 2 = - \frac{1}{2} x - 1 \\ y = - \frac{1}{2} x + 1[/tex]
Answer:
[tex]y=-\frac{1}{2}x+1[/tex]
Step-by-step explanation:
The equation of a line is [tex]y=mx+b[/tex] where m is the pending and b is the y intercept,
First we are going to calculate m:
If you have two points [tex]A=(x_{1},y_{1})\\B=(x_{2},y_{2})[/tex],
[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
Now we have, A=(-6,4) and B=(-2,2),
[tex]x_{1}=-6 , y_1=4\\x_2=-2, y_2=2[/tex] replacing in the formula:
[tex]m=\frac{2-4}{(-2)-(-6)} \\\\m=\frac{-2}{4} \\\\m=-\frac{1}{2}[/tex]
Then [tex]y=-\frac{1}{2}x+b[/tex]
We have to find b, we can find it replacing either of the points in [tex]y=-\frac{1}{2}x+b[/tex]
Replacing with (-2,2),
[tex]y=-\frac{1}{2}x+b\\2=-\frac{1}{2}.(-2)+b\\2=1+b\\2-1=b\\1=b[/tex]
or replacing with (-6,4)
[tex]y=-\frac{1}{2}x+b\\4=-\frac{1}{2}.(-6)+b\\4=3+b\\4-3=b\\1=b[/tex]
You can see that the result is the same, then the equation of the line is:
[tex]y=-\frac{1}{2}x+1[/tex]